Circadian Blood Pressure Variations Computed From 1.7 Million Measurements in an Acute Hospital Setting. (16th August 2019) - Mahdi, Adam; Watkinson, Peter; McManus, Richard J; Tarassenko, Lionel
Abstract: BACKGROUND: Knowledge of the circadian blood pressure (BP) variations in the acute hospital setting is very limited. METHODS: This is a retrospective analysis of BP data for in-hospital patients stratified by age and sex. We used data collected with the help of a standardized electronic health record system between March 2014 and April 2018 on the adult general wards in 4 acute hospitals in Oxford, UK. RESULTS: A total of 41, 455 unique patient admissions with 1.7 million sets of vital-sign measurements have been included in the study. The typical 24-hour systolic BP profile (dipping pattern during sleep followed by a gradual increase during the day) was only seen in the younger age groups (up to 40–49 for men and 30–39 for women). For older age groups, there was a late nocturnal rise in systolic BP, the amplitude of which increased with age. The late nocturnal BP rise above the age of 50 was seen whether or not the patient was treated for or previously identified with hypertension. CONCLUSION: Hospitalized patients' circadian patterns of BP largely mirror those found in the community. High-quality hospital data may allow for the identification of patients at significant cardiovascular risk through either opportunistic screening or systematic screening.